An uncontrolled, feasibility study of a group intervention to reduce hepatitis C transmission risk behaviours and increase transmission knowledge among women who inject drugs. (4th March 2017) - Gilchrist, G.; Tirado-Munoz, J.; Taylor, A.; Fischer, G.; Moskalewicz, J.; Köchl, B.; Giammarchi, C.; Dabrowska, K.; Shaw, A.; Munro, A.; Di Furia, L.; Torrens, M.
Abstract: Aims: This study aimed to develop and test the feasibility, acceptability and initial effectiveness of a three-session psychosocial group intervention to reduce hepatitis C risk behaviours and increase hepatitis C transmission knowledge among women who inject drugs in five European cities/towns. Methods: An uncontrolled, field effectiveness study of a psychosocial group intervention. Hepatitis C virus (HCV) transmission knowledge, sexual and drug risk behaviours and depressive symptoms were assessed at baseline and one-month post-intervention. Intention-to-treat analyses were conducted. Findings: One-month post-intervention, a significant increase was reported in HCV transmission knowledge and in the number of new and unused needles/syringes used to inject. There were significant reductions in the sharing of spoons/containers for mixing that had been used by someone else, sharing of filters, cookers, spoons or water with someone who was hepatitis C positive and the use of alcohol swabs following injection. Conclusions: The intervention showed promising results in reducing some hepatitis C injecting risk behaviours and increasing hepatitis C transmission knowledge among women who inject drugs. These preliminary findings suggest that it is feasible to deliver the intervention in drug treatment settings, and that the intervention was acceptable to both participants and staff.